Discovery of highly potent SARS-CoV-2 nsp14 methyltransferase inhibitors based on adenosine 5'-carboxamides - Kocek, Hugo; Chalupská, Dominika; Dejmek, Milan; Dvořáková, Alexandra; Zgarbová, Michala; Šála, Michal; Chalupský, Karel; Krafčíková, Petra; Otava, Tomáš; Drexler, Matúš; Procházková, Eliška; Klepetářová, Blanka; et al. (RSC medicinal chemistry, 2024)
The emergence of SARS-CoV-2, the causative agent of COVID-19, has highlighted the need for advanced antiviral strategies. Targeting the coronaviral methyltransferase nsp14, which is essential for RNA capping, offers a promising approach for the development of small-molecule inhibitors. We designed and synthesized a series of adenosine 5'-carboxamide derivatives as potential nsp14 inhibitors and identified coumarin analogs to be particularly effective. Structural modifications revealed the importance of the 5'-carboxyl moiety for the inhibitory activity, showing superior efficacy compared to other modifications. Notably, compound 18l (HK370) demonstrated high selectivity and favorable in vitro pharmacokinetic properties and exhibited moderate antiviral activity in cell-based assays. These findings provide a robust foundation for developing targeted nsp14 inhibitors as a potential treatment for COVID-19 and related diseases.